COLLECTIVE CONSTRUCTION OF A FLOWCHART FOR FOLLOW-UP OF PREGNANT WOMEN WITH SYPHILIS IN THE MUNICIPALITY OF SÃO JOSÉ-SC. - da Silveira Silva, Vanessa Beatriz; Stein Backes, Marli Terezinha; de Freitas de Mello, Janei; Scremin Magagnin, Jardel; Menezes Brasil, Joyce; da Silva, Catarina Izabel; dos Santos, Cleverson (Cogitare Enfermagem, 2020)
Objective: To instruct, with a flowchart and Standard Operating Procedure, nurses from Primary Health Care, in order to monitor cases of gestational syphilis. Method: Qualitative research, action-research type, practical-educational modality. Attendees: Representatives of the Epidemiological Surveillance, Women's Health Program, Primary Health Care, nurses from the Family Health Strategy and the medical staff. Made in the city of São José-SC, in October 2017. Results: An instrument was developed to assist pregnant women with a rapid reagent test for syphilis. Conclusion: The participants working in the primary care assistance practice, through a dynamic process, allowed legitimacy, seeking to meet the demands of the services and the professionals. The speed in the diagnosis, monitoring and treatment of syphilis in pregnancy are related to the proper management, associated with actions, strategies and updates, providing qualified assistance during the gestational period, to effectively eradicate congenital syphilis.